Immunomodulatory properties of extracellular vesicles isolated from bone marrow of patients with neuroblastoma: role of PD-L1 and HLA-G - Marimpietri, Danilo; Corrias, Maria Valeria; Tripodi, Gino; Gramignoli, Roberto; Airoldi, Irma; Morandi, Fabio (Frontiers in Immunology, 2024)
Extracellular vesicles (EVs) can be released by any cell and are crucial for cell-to-cell communications. EVs have been characterized in patients with solid and hematological tumors, where they play an important role in tumor progression and metastasis. EVs may express different surface proteins derived from the parental cells, including immunomodulatory molecules, such as HLA-G and PD-L1. We found a higher expression of CD56 on EVs derived from bone marrow (BM) of patients with neuroblastoma (NB) than in those from healthy donors (HD). However, CD56 expression was not dependent on BM infiltration of NB cells. Moreover, the analysis of GD2 expression revealed that only a small fraction of EVs was released by infiltrating NB cells, whereas the majority may derive from BM-resident cells. BM-derived EVs from NB patients display a higher expression of HLA-G and PD-L1 than those derived from HD. Nonetheless, such EVs are able to modulate T cell immune responses. We measured a robust response, in vitro, towards a common bacterial antigen, including the release of GM-CSF and pro-inflammatory cytokines, like IFN-α and IL-6, from mononuclear cells. Some of these immunomodulatory features are dependent on the expression of HLA-G and PD-L1, whereas others may rely on other mechanism(s). Finally, a high expression of CD56, HLA-G and PD-L1 on BM-derived EVs may represent a good prognostic factor. In conclusion, we described the presence of HLA-G and PD-L1-bearing EVs in the BM of NB patients, which may represent a mechanism performed by resident BM cells to counteract the inflammation occurring in the BM microenvironment of NB patients.